2018
DOI: 10.1111/inr.12449
|View full text |Cite
|
Sign up to set email alerts
|

Shaping nursing profession regulation through history – a systematic review

Abstract: Understanding factors that socially, legislatively and politically have influenced the development of regulatory bodies over time helps to mould local, national and international policies that have a stronger impact on health worldwide. To achieve this, there must be effective cooperation among systems of nursing regulations globally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
0
21
0
3
Order By: Relevance
“…Nurses were encouraged to participate in a global health system, decision‐making, and practice‐based research . To set the common standards, the minimum requirement for the nursing education in European countries was shifted to the baccalaureate degree . Nontraditional educational practices were introduced to develop clinical reasoning, grounded in evidence, necessary for nurses to practice autonomously in reformed health care environments and to overcome domination of physicians .…”
Section: Introductionmentioning
confidence: 99%
“…Nurses were encouraged to participate in a global health system, decision‐making, and practice‐based research . To set the common standards, the minimum requirement for the nursing education in European countries was shifted to the baccalaureate degree . Nontraditional educational practices were introduced to develop clinical reasoning, grounded in evidence, necessary for nurses to practice autonomously in reformed health care environments and to overcome domination of physicians .…”
Section: Introductionmentioning
confidence: 99%
“…Este fortalecimiento organizativo y político respecto al ejercicio liberal de la profesión, la introducción al mercado laboral de sus servicios expertos, la construcción de una identidad, el gobierno y la legislación fueron una expresión de su autonomía. Todo esto se percibe como un progreso para la profesión de Enfermería (18)(19)(20) .…”
Section: Discussionunclassified
“…Estos tres elementos: autorregulación, autonomía e identidad, forman un circulo virtuoso debido a su interdependencia, en que uno favorece la consolidación del otro, en un proceso sinérgico como señalan algunos autores (18,20,21) . Sin duda, el respaldo legal a la función de la enfermera es un avance para la profesión y constituye un hito político importante para el mandato social de la Enfermería como profesión en el país y en Latinoamérica.…”
Section: Discussionunclassified
“…Nurse regulation carries a history of episodes of change and adjustment during its evolution in Europe. 21 The outcomes of the exercise reported in this paper suggest the need for host countries to develop regulatory structures which are valid and transferable, but which also accommodate and facilitate the mobility of nurse refugees with missing or unverifiable documentation. The exercise also revealed that existent processes which address the challenges associated with missing, unverifiable or untraceable qualification rely heavily on panels of credential evaluators and experts.…”
Section: Conclusion and Recommendationsmentioning
confidence: 93%